EVALUATION OF GRAIN QUALITY PROPERTIES OF SOME IRAQI AND ICARDA SELECTED DURUM WHEAT CULTIVARS - Ahmed Salih Khalaf (Mesopotamia Journal of Agriculture)
Four samples of Iraqi durum wheat cultivars and six selected varieties of ICARDA were involved in this study, for their grain quality tests and flour rheological properties comparison. Their gliadin electrophoresis was also conducted. Results showed a significant variation among tested varieties for the grain characters, protein quantity and quality in term of SDS-sedimentation test. The highest levels of SDS-values and SDS-index were recorded for Haurani, Korifla, Gidara-2, and Om rabi-5, but Caronia is the best in pigments. Among the tested cultivars, Iraqi cultivar Caronia resemble the Syrian one (Haurani) in giving positive reaction with phenol test. Concerning with the gliadin subunits electrophoregrams patterns, cultivars can be classified into two groups, those possess the gamma gliadin components designated 45 and the linked omega gliadin 35, include cultivars (Caronia, Acsad-65, Simeto, Creso, Om rabi-5, Haurani, Korifla and Gidara-2, while those possess gamma gliadin 42, included cultivars (Waha, , and Cham-5).